2020
DOI: 10.1038/s41598-020-76653-7
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in detrusor contractility in rat model of bladder cancer

Abstract: Urinary incontinence of idiopathic nature is a common complication of bladder cancer, yet, the mechanisms underlying changes in bladder contractility associated with cancer are not known. Here by using tensiometry on detrusor smooth muscle (DSM) strips from normal rats and rats with bladder cancer induced by known urothelial carcinogen, N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN), we show that bladder cancer is associated with considerable changes in DSM contractility. These changes include: (1) decrease in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The urinary bladder smooth muscle is excitable by multiple ion channels, primarily calcium channels like Cav1, Cacna1c, Atp2b4, and transient receptor potential (Trp) channels [43], many of which showed, in our study, changes in expression and methylation pattern in invasive tumors. Changes in bladder contractility is a known complication of BC, and alterations in detrusor contractility was found in the rat model of bladder cancer, confirming our findings and stressing the importance of neuro-muscle disturbances in BC [44].…”
Section: Discussionsupporting
confidence: 90%
“…The urinary bladder smooth muscle is excitable by multiple ion channels, primarily calcium channels like Cav1, Cacna1c, Atp2b4, and transient receptor potential (Trp) channels [43], many of which showed, in our study, changes in expression and methylation pattern in invasive tumors. Changes in bladder contractility is a known complication of BC, and alterations in detrusor contractility was found in the rat model of bladder cancer, confirming our findings and stressing the importance of neuro-muscle disturbances in BC [44].…”
Section: Discussionsupporting
confidence: 90%
“…These pathologies can be interconnected. As mentioned above, diabetes mellitus is a risk factor for bladder cancer prognosis [ 64 ], and urinary incontinence is a common complication of bladder cancer [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic urinary incontinence is a common complication of BLCA. Studies have shown that BLCA is associated with dramatic changes in the contractility of the smooth muscle of the detrusor ( 33 , 34 ). One of the features of cancers that occur in the bladder is that the tumor invades and crosses the biophysical barrier of the smooth muscle ( 35 ).…”
Section: Discussionmentioning
confidence: 99%